(3GdEYdGe GdEbdjej (B:s (3OQGSI fXQjI h ejOGfjI (B/s - (3GdeSdej, EHQGgje YHO Gddgs ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ,s, 2004)
(3aj gPG GdcJGH jVe GdYfGUQ GdGQHYI GhdG HfGA fXQi dJYQja GdGYdGe GdEbdjej Ke JMOjO hXGFag aj GdeLJeY GdeYGUQ KGfjG eSM dhSGFd GdGYdGe GdGbdjejI HeG ajgG ef UMGaI h QGOjh h JdjaRjhf aj HYV Ohd GdYGde GdeJbOeI GdJj JLJeY ajgG GdhSGFd GdKdGK eYG KGdKG JGUjd JGQjNj dfTGI GdGYdGe GdGbdjej aj eUQ h JWhQg QGHYG OQGSI ejOGfjI Yf GdbQGAI h GdGSJeGQI h GdeTGgOI dhSGFd GdGYdGe GdGbdjejI aj GMO GdeLJeYGJ GdJj JJhGaQ ajgG gPg GdhSGFd GdKdGK eLJeYI aj eUQs
Keywords: (3GdEYdGes; (3GdEYdGe GdEbdjejs